2021
DOI: 10.1210/clinem/dgab836
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Papillary Thyroid Cancer: A Systematic Appraisal of Risk Factors

Abstract: Background Thyroid cancer recurrence is associated with increased mortality and adverse outcomes. Recurrence risk is currently predicted using clinical tools, often restaging patients after treatment. Detailed understanding of recurrence risk at disease-onset could lead to personalised and improved patient care. Objective To perform a comprehensive bioinformatic and experimental analysis of 3 levels of genetic change (mRNA, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Moreover, Sponziello et al observed that FN1 was increased in aggressive thyroid cancer and governed thyroid cancer cells proliferation, adhesion, migration, and invasion(Sponziello et al 2016). Additionally, according to Nieto et al's research, FN1 was signi cantly upregulated in recurrent thyroid cancer and impacted cellular migration, highlighting it as a potential prognostic biomarker(Nieto et al 2022).In agreement with above study, we revealed that FN1 was signi cantly upregulated in PTC. Moreover, we found FN1 was the LINC02454 co-expressed gene involved in ECM − receptor interaction pathway.…”
supporting
confidence: 90%
“…Moreover, Sponziello et al observed that FN1 was increased in aggressive thyroid cancer and governed thyroid cancer cells proliferation, adhesion, migration, and invasion(Sponziello et al 2016). Additionally, according to Nieto et al's research, FN1 was signi cantly upregulated in recurrent thyroid cancer and impacted cellular migration, highlighting it as a potential prognostic biomarker(Nieto et al 2022).In agreement with above study, we revealed that FN1 was signi cantly upregulated in PTC. Moreover, we found FN1 was the LINC02454 co-expressed gene involved in ECM − receptor interaction pathway.…”
supporting
confidence: 90%
“…We propose that extensive dysregulation of endocytic genes in PTC results in NIS mislocalisation away from the PM and reduced radioiodide uptake, leading to a greater number of treatment-resistant tumour cells and increased risk of recurrence. Early detection of PTC recurrence has been shown to improve patient outcomes, but there is still a need for new biomarkers ( 53 ). In this study construction of a 30-endocytic gene risk score classifier for recurrence had higher specificity and sensitivity than single gene biomarkers, as well as being an independent predictor of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Xavier et al found that FN1 was closely associated with macrophage M2, and that its increased expression played a pivotal role in tumor resistance (Xavier et al, 2021). Moreover, upregulation FN1 expression was also strongly implicated in recurrence in hepatocellular carcinoma, endometrial cancer, and thyroid cancer (de Andrade et al, 2021; Kim et al, 2020; Nieto et al, 2021). Combined with our analysis, FN1 may promote invasion and recurrence of AMs by regulating EMT process and macrophages polarization, and it can be used as a promising biomarker for the diagnosis and therapeutic options of AMs.…”
Section: Discussionmentioning
confidence: 99%